2002
DOI: 10.1103/physrevb.66.165422
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and electronic properties of ultrathin crystalline silica epilayers on a Mo(112) substrate

Abstract: Ultrathin crystalline silica layers grown on a Mo͑112͒ substrate have been shown to be a useful silica model oxide support in surface science model catalyst studies. As the oxide support material plays an important role in the catalytic process, a multitechnique surface science study is presented to characterize the morphological and electronic properties of the heteroepitaxial system SiO 2 /Mo(112). The long-range order of the silica epilayer which grows commensurate with a c(2ϫ2) surface unit mesh on the Mo͑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
106
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(115 citation statements)
references
References 58 publications
(48 reference statements)
9
106
0
Order By: Relevance
“…In this model, the forth ("apical") oxygen atom of each tetrahedra (which remains uncoordinated in the case of a monolayer silica film) must be stabilized either by hydrogen, thus forming silanol (Si-OH) groups, or shared with further silica layers. Since neither silanol nor hydroxyl species were observed on these films [18], this implied that the silica film was of several layers in thickness.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In this model, the forth ("apical") oxygen atom of each tetrahedra (which remains uncoordinated in the case of a monolayer silica film) must be stabilized either by hydrogen, thus forming silanol (Si-OH) groups, or shared with further silica layers. Since neither silanol nor hydroxyl species were observed on these films [18], this implied that the silica film was of several layers in thickness.…”
mentioning
confidence: 99%
“…2a). In addition, well-resolved images of antiphase domain boundaries (APDB) running along the 10] 1 [ direction as predicted by LEED studies [18] were obtained as indicated in Fig. 2a.…”
mentioning
confidence: 99%
See 3 more Smart Citations